Sarcopenia is associated with increased major adverse cardiovascular event incidence in maintenance hemodialysis patients: a prospective cohort study and mediation analysis - Jiang, Lu; Wang, Zitao; Yuan, Mengxuan; Wang, Weiping; Wu, Buyun; Mao, Huijuan (Frontiers in Nutrition, 2024)
Few studies have investigated the relationship between sarcopenia and the incidence of major adverse cardiovascular events (MACE), which are common complications in maintenance hemodialysis (MHD) patients. This study thus explored the association between sarcopenia and MACE in a prospective cohort with mediation analysis.Adult MHD patients were screened. The exposure was sarcopenia, as defined by the 2019 Asian Working Group. The primary endpoint was the occurrence of MACE, defined as the composite of all-cause mortality or hospital admission with a primary diagnosis of acute myocardial infarction, stroke, or heart failure during a 3-year follow-up period. Multivariate Cox regression analyses were used to test the association between sarcopenia and subsequent MACE incidence. Mediation analyses were used to investigate whether potential mediators influenced the association between sarcopenia and MACE. Of the 230 patients enrolled, 57% were male. The prevalence of sarcopenia was 45.2%. The presence of sarcopenia was significantly correlated with age (Spearman's r = 0.47, P< 0.001), C-reactive protein (Spearman's r = 0.13, P = 0.044), serum albumin (Spearman's r = -0.22, P< 0.001), 25(OH) vitamin D (Spearman's r = -0.26, P< 0.001), and coronary artery calcification score (Spearman's r = 0.20, P = 0.002). Over the 3-year follow-up period, MACE were observed in 59/104 (56.7%) patients with sarcopenia and 38/126 (30.2%) patients without sarcopenia (log-rank P< 0.001). After accounting for potential confounders, patients with sarcopenia presented a 66% (4-168%, P = 0.035) increase in their risk of MACE incidence as compared to non-sarcopenic individuals. However, adjusted mediation analyses did not detect any indication of a causal mediation pathway linking the effects of sarcopenic status on coronary artery calcification score, C-reactive protein, serum albumin, or 25(OH) vitamin D levels to MACE outcomes. Conversely, sarcopenia exhibited a potential direct effect (average direct effect range: -1.52 to -1.37, all P< 0.05) on MACE incidence.Conclusions: These results revealed that the presence of sarcopenia was associated with a higher incidence of MACE in MHD patients. The putative effects of sarcopenia on this cardiovascular endpoint are possibly not mediated by any causal pathways that include vascular calcification, inflammation, hypoalbuminemia, or vitamin D.